The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/01.aoa.0000552897.80673.4c
|View full text |Cite
|
Sign up to set email alerts
|

Do Time of Birth, Unit Volume and Staff Seniority Affect Neonatal Outcome in Deliveries at ≥34+0 Weeks of Gestation?

Abstract: Objective We investigated whether time of birth, unit volume, and staff seniority affect neonatal outcome in neonates born at ≥34 +0 weeks of gestation.Design Population-based prospective cohort study.Setting Ten public hospitals in the Austrian province of Styria.Sample A total of 87 065 neonates delivered in the period 2004-2015.Methods Based on short-term outcome data, generalised linear mixed models were used to calculate the risk for adverse and severely adverse neonatal outcomes according to time of birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 31 publications
2
9
3
Order By: Relevance
“…The major body of existing literature on weekend effect in the field of perinatal medicine is focused on neonatal mortality 4‐9,30‐32 . The result of this study is consistent with the majority of studies conducted in the twenty‐first century 4‐9 in that it shows no increased risk for neonatal mortality among infants who were born during the weekend.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The major body of existing literature on weekend effect in the field of perinatal medicine is focused on neonatal mortality 4‐9,30‐32 . The result of this study is consistent with the majority of studies conducted in the twenty‐first century 4‐9 in that it shows no increased risk for neonatal mortality among infants who were born during the weekend.…”
Section: Discussionsupporting
confidence: 84%
“…Among studies that employed the same or similar outcomes, the of this study contradict some previous studies conducted in European countries which found no significant association between weekend delivery and adverse outcomes. 4,10,11,13,32 An important factor that may explain the discrepancy between the current findings and previous research is the differences in the health care system, such as practice guidelines, access to hospitals and insurance coverage. For example, having adequate ANC was significantly associated with delivering during the weekdays (x = 373.21, P < .001) and was protective against having any neonatal adverse outcomes (OR 0.88; 95% CI 0.87-0.89).…”
Section: T a B L Econtrasting
confidence: 90%
See 1 more Smart Citation
“…Reif et al identified that while afternoon and nighttime births were associated with an increase in adverse neonatal outcomes, births occurring in a tertiary or perinatal care center and birth attendance by a senior staff member appeared to have a protective effect in high risk births despite the higher volume of patients cared for in these institutions and the potential for reduced personnel coverage during off hours 19 . This was observed in our data set, as nighttime births had a trend towards significance in having a full resuscitation team (p = 0.08), while daytime births were more likely to have a smaller resuscitation team.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent literature suggests potentially worsened outcomes of neonates resuscitated at birth during evening and nighttime hours 16 , 17 , 18 , 19 . Shift length, shifts scheduled outside of typical daytime hours, and physician fatigue can result in increased patient load and capacity strain on perinatal providers during nighttime hours and potentially contribute to medical errors and poor outcomes 20 , 21 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%